Pt-Decorated Graphene Gate AlGaN/GaN MIS-HEMT for Ultrahigh Sensitive Hydrogen Gas Detection - Ahn, Jungho; Kim, Dahee; Park, Kyung Ho; Yoo, Geonwook; Heo, Junseok (IEEE Transactions on Electron Devices, 2021)
Hydrogen fuel has attracted significant attention as an alternative clean energy for hydrogen vehicles and household fuel systems and has been expected to be pervasive. Thus, compact, low-power, and highly sensitive hydrogen sensors capable of being embedded in Internet-of-Things devices are in demand. In this work, an ultrahigh sensitive hydrogen sensor operating at room temperature based on the Pt-decorated graphene (Pt/Gr) gate AlGaN/GaN metal-insulator-semiconductor high electron mobility transistor (MIS-HEMT) is presented. The proposed unique gate structure of island-like Pt on graphene not only modulates the density of 2-D electron gas (2DEG) but also provides efficient diffusion of hydrogen ions into the gate even at very low concentrations (< 1 ppm) of hydrogen. The fabricated Pt/Gr gate AlGaN/GaN MIS-HEMT hydrogen sensor shows a remarkably high response of ∼ 1.6× 107 in a hydrogen concentration of 1000 ppm at room temperature. Upon exposure of at most 1 ppm hydrogen gas, the current increases significantly by a factor of 15.4, exhibiting an unprecedentedly high hydrogen response. Furthermore, the proposed AlGaN HEMT architecture has an outstanding hydrogen selectivity and insensitivity to NH3, H2S, and CO gases at the same time.
Keywords: 2-D electron gas (2DEG); Current increase; Hydrogen concentration; Hydrogen gas detection; Hydrogen selectivity; Hydrogen vehicles; Low concentrations; Metal-insulator-semiconductor high-electron mobility transistors (MIS-HEMT); AlGaN; hydrogen sensing; metal-insulator-semiconductor high electron mobility transistor (MIS-HEMT); Pt/graphene gate